Improving Fiqh Learning Outcomes Through a Mind Mapping-Based Flipped Classroom - Pristian Hadi Putra; Uun Fauzanah Fitri; Adi Putra; Endah Silawati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The learning outcomes of Grade VIII students in the Fiqh subject at MTsN 6 Kerinci remain relatively low. This is due to the use of conventional teaching models that fail to facilitate studentsÔÇÖ engagement actively in the learning process. To address this issue, a flipped classroom model integrated with mind mapping techniques was implemented to enhance studentsÔÇÖ understanding and academic performance. This study aims to determine the effect of the flipped classroom model based on mind mapping on students' learning outcomes in Fiqh. The method used is quantitative with a quasi-experimental approach, employing a Pretest-Posttest Control Group Design. The research sample consisted of 30 students divided into two classes: an experimental class that received the flipped classroom model based on mind mapping, and a control class that used a conventional teaching model. Data were collected through pretest and posttest assessments and analyzed by using a t-test. The results of the partial statistical analysis (t-test) showed that the flipped classroom model based on mind mapping had a positive and significant effect on studentsÔÇÖ learning outcomes in the Fikih subject for Grade VIII at MTsN 6 Kerinci. This is evidenced by the hypothesis test result of t count > t table = 2.463 > 1.771, with a significance value of 0.02 < 0.05, indicating that Ha is accepted and Ho is rejected. This confirms that the flipped classroom model based on mind mapping significantly and positively influences the improvement of Fiqh learning outcomes among Grade VIII students at MTsN 6 Kerinci.